World-class long-distance running performances are best predicted by volume of easy runs and deliberate practice of short-interval and tempo runs - Casado, A.; Hanley, B.; Santos-Concejero, J.; Ruiz-Pérez, L. M. (The Journal of Strength and Conditioning Research, 2019)
The aim of this novel study was to analyze the effect of deliberate practice (DP) and easy continuous runs completed by elite-standard and world-class long-distance runners on competitive performances during the first 7 years of their sport careers. Eightyfive male runners reported their best times in different running events and the amounts of different DP activities (tempo runs and short- and long-interval sessions) and 1 non-DP activity (easy runs) after 3, 5, and 7 years of systematic training. Pearson`s correlations were calculated between performances (calculated using the International Association of Athletics Federations` scoring tables) and the distances run for the different activities (and overall total). Simple and multiple linear regression analysis calculated how well these activities predicted performance. Pearson`s correlations showed consistently large effects on performance of total distance (r >/- 0.75, p < 0.001), easy runs (r >/- 0.68, p < 0.001), tempo runs (r >/- 0.50, p < 0.001), and short-interval training (r >/- 0.53, p < 0.001). Long-interval training was not strongly correlated (r >/- 0.22). Total distance accounted for significant variance in performance (R² >/- 0.57, p < 0.001). Of the training modes, hierarchical regression analysis showed that easy runs and tempo runs were the activities that accounted for significant variance in performance (p < 0.01). Although DP activities, particularly tempo runs and short-interval training, are important for improving performance, coaches should note that the non-DP activity of easy running was crucial in better performances, partly because of its contribution to total distance run.